SISTEM PENGENDALIAN INTERN PENERIMAAN KAS - Katarina, Desi; ES Samosir, Hendrik; Silaban, Adanan (Jurnal Akuntansi Nommensen, 2022)
This research aims to determine the extent to which the internal control system for cash receipts at PT. Reycom Document Solutions Medan Branch in carrying out its business activities in order to achieve company goals. The data source used in this research is primary data. With descriptive data analysis techniques and comparative analysis techniques, descriptive data analysis is by first collecting data, classifying data and interpreting data so that it can provide a clear picture of the problem being studied. Meanwhile, comparative data analysis is drawing conclusions from observed facts and their truth has been tested by comparing theories which are general truths with field data, with the hope of being able to draw conclusions and put forward suggestions for improvements to weaknesses and errors found in internal control of cash receipts. The results of this research show that the internal control system for cash receipts at PT. Reycom Document Solutions Medan Branch has not fully fulfilled the elements of internal control, because there are still several things that are not in accordance with existing theory. These include the fact that there are still duplicate tasks between the finance and accounting sections which are handled by the finance admin, unannounced checks on employee work have not been implemented and there is also no special section formed to exercise control over the company.